2020
DOI: 10.1155/2020/2124694
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Stress Effects on Smooth Blasting: Model Test and Analysis

Abstract: Most of the roadway excavation is completed by the drilling and blasting method. With the increase of buried depth, the existence of ground stress will generate a significant impact on the rock blasting, especially on the smooth blasting. In this study, self-made homogeneous similar materials and digital image correlation methods were used to determine influence of ground stress on the smooth blasting under uniform explosive charge parameters and various in situ stress conditions. The results show that the cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…The research showed that the circumferential hole with a slotted tube charging structure significantly improved the overbreak phenomenon in the fault stratum. Yang et al [17] adopted self-made uniform similarity materials and digital image correlation methods and found that with the increase in buried depth, the ground stress exhibited a significant effect on smooth blasting, and the fracture surface tended to be flat with the increase in in situ stress. Qi et al [18] used the finite element numerical simulation software ANSYS/LS-DYNA to simulate the blasting process of the coupled charge in the peripheral holes in smooth blasting.…”
Section: Introductionmentioning
confidence: 99%
“…The research showed that the circumferential hole with a slotted tube charging structure significantly improved the overbreak phenomenon in the fault stratum. Yang et al [17] adopted self-made uniform similarity materials and digital image correlation methods and found that with the increase in buried depth, the ground stress exhibited a significant effect on smooth blasting, and the fracture surface tended to be flat with the increase in in situ stress. Qi et al [18] used the finite element numerical simulation software ANSYS/LS-DYNA to simulate the blasting process of the coupled charge in the peripheral holes in smooth blasting.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the conclusions of the previous literatures. 13,14 However, compared with the main crack length in specimen H4, the main crack length in specimen H12 is increased by 24.1 mm, meaning that the static stress can promote crack propagation again when the static stress exceeds a certain value. This phenomenon is different from the previous findings.…”
Section: Crack Propagationmentioning
confidence: 98%
“…11,12 The model tests of smooth blast and presplitting blast under uniaxial loading were carried out, with results indicating that static stress has an essential effect on smooth blasting and presplitting blasting. [9][10][11][12][13] In addition, the single hole blast experiments and slit charge blast experiments were conducted under static stress using the caustic method. The results show that compressive stress increases the fractal dimension and promotes crack propagation when the compressive stress is parallel to the main crack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, photoelasticity and caustics methods meet difficulties in measurements near the borehole because data acquisition of isochromatic fringes in photoelasticity and shadow patterns in caustics method is very difficult in such an extreme condition. Digital image correlation (DIC) becomes a very effective method to study blast-induced stress waves [19,20], but this method needs speckles or reference points on specimen surface and does not work well for blast gases. Schlieren method can visualize propagation of shock waves and blast-induced products near the borehole because this method is sensitive to gas dynamics in transparent media.…”
Section: Introductionmentioning
confidence: 99%